2021
DOI: 10.3390/insects12080756
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Soy Leaf Flavonoids on Pea Aphid Probing Behavior

Abstract: Flavonoids detected in soybean Glycine max (L.) Merr. (Fabaceae) cause various alterations in the metabolism, behavior, and development of insect herbivores. The pea aphid Acyrthosiphon pisum (Harris) (Hemiptera: Aphididae) poses potential threat to soybeans, but the effect of individual flavonoids on its feeding-associated behavior is relatively unknown. We monitored probing behavior (stylet penetration activities) of A. pisum on its preferred host plant, Pisum sativum L. untreated (control) and treated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 95 publications
0
17
0
Order By: Relevance
“…Recent studies have shown that kaempferol and apigenin treated pea plants exhibited a decrease in the intensity of aphid-sap ingestion, although treatment with these flavonoids did not prohibit aphid attack. Also kaempferol made the finding of sap-transporting vessels more difficult for aphids, underlining a protection role to biotic stress (Stec et al, 2021). Interestingly kaempferol together with quercetin glycosides such as rutin are found in the aerial parts of lentil plants, where the later compounds represent about 73% of the total determined flavonoids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown that kaempferol and apigenin treated pea plants exhibited a decrease in the intensity of aphid-sap ingestion, although treatment with these flavonoids did not prohibit aphid attack. Also kaempferol made the finding of sap-transporting vessels more difficult for aphids, underlining a protection role to biotic stress (Stec et al, 2021). Interestingly kaempferol together with quercetin glycosides such as rutin are found in the aerial parts of lentil plants, where the later compounds represent about 73% of the total determined flavonoids.…”
Section: Discussionmentioning
confidence: 99%
“…Flavonoids are regarded as secondary antioxidants that complement the primary antioxidants upon large alterations in redox homeostasis that depress the activity of the later while promoting the biosynthesis of the flavonoid antioxidants (Agati et al, 2020). Noteworthy that such flavonoids were previously shown to be linked to resistant genotypes (Togola et al, 2020;Stec et al, 2021) indicating an innate biotic stress response to aphid infestation. However what molecular mechanisms and chemical signals elicit this response remains to be explored.…”
Section: Discussionmentioning
confidence: 99%
“…Non-mycorrhizal C. aurantium plants were sprayed with six different compounds (kaempferol, luteolin, diconyferil alcohol, neohesperidin, malic acid, cinnamic acid) at a concentration of 0.5 mM in the range of other treatments with flavonoids (Wachter et al, 1999;Stec et al, 2021). Treatments were grouped according to the solvent used as a control.…”
Section: Antibiotic Properties Of Phenylpropanoids Derivative Compoun...mentioning
confidence: 99%
“…Kasmiyati et al (2020) reported induced polyploidy using colchicine be able to increase flavonoid content. Furthermore, flavonoid affect the behavior of aphid especially it could decrease sap ingestion activity (Goławska et al, 2014;Stec et al, 2021). Considering that aphid is a kind of pest which is very often attacking beans and very difficult to manage, this result is an important progress in developing an aphid-resistant crop.…”
Section: Incidence Of Cowpea Aphid (Aphis Craccivora) On Cowpea Podsmentioning
confidence: 99%